Comparison of two sampling schemes in estimating the stress-strength reliability under the proportional reversed hazard rate model - Sadeghpour, Amineh; Nezakati, Ahmad; Salehi, Mahdi (Statistics, Optimization & Information Computing, 2020)
In this paper, point and interval estimation of stress-strength reliability based on lower record ranked set sampling scheme under the proportional reversed hazard rate model are considered. Maximum likelihood, uniformly minimum variance unbiased, and Bayesian estimators of R are derived and their performances are compared. Various confidence intervals for the parameter R are constructed, and compared based on the simulation study. Moreover, the record ranked set sampling scheme is compared with ordinary records in case of interval estimations. Finally, a data set has been analyzed for illustrative purposes.